Business Management - Alfai, Mujid; Mulyani, Ana Susi (Indonesian Journal of Advanced Research, 2023)
The business management discussed in this article includes the functions and roles of management, company organization, management of the production of goods and services, and management of human resources. The main focus is understanding how effective management can improve company performance through strategic planning, good organization, efficient production supervision, and human resource management oriented towards developing employee potential. This article details the importance of integrating all these aspects in achieving business goals and increasing a company's competitiveness in a dynamic business environment. This article was created using the Literature Study Method by searching from book sources related to Business Management which were then studied and collected into data. In business management, the role and function of management is very crucial. Management is responsible for organizing the company, managing the production of goods and services, and managing human resources. By designing efficient organizational structures, coordinating production processes, and leading human resource development, management helps achieve business goals in a sustainable manner. Overall, the role of integrated management plays a key role in the success and growth of the business.